Development and validation of the global diet quality score (GDQS) for children 5 to 9 years of age - Arsenault, Joanne E.; Ali, Nazia Binte; Atayde, Agata M. P.; Batis, Carolina; Becquey, Elodie; Bromage, Sabri; Deitchler, Megan; Diop, Loty; Gelli, Aulo; Castellanos Gutierrez, Anali; Kehoe, Sarah H.; Krishnaveni, Ghattu V.; et al. (Oxford University Press, 2025)
Objective The purpose of the study was to develop and validate a Global Diet Quality Score (GDQS) for children aged 5–9 years adapted from the existing GDQS developed for adults.